THE RELATIONSHIP BETWEEN FINANCIAL RISK MANAGEMENT AND CORPORATE RESILIENCE DURING A CRISIS: A COMPREHENSIVE LITERATURE REVIEW - Musilatin Nikmah; Hety Devita; Muhamad Eko Wahyu Umaryadi; FX. Nanang Sujatmiko (International Journal Of Humanities, Social Sciences And Business (INJOSS), 2026)
This article aims to analyse the relationship between financial risk management and corporate resilience during times of crisis through a comprehensive literature review. The findings indicate that financial risk management plays a strategic role in strengthening corporate resilience, particularly through the stabilisation of cash flows, the protection of liquidity, the control of loss exposure, the improvement of decision-making quality, and the strengthening of risk governance. The literature also indicates that companies which implement integrated risk management tend to be more resilient in the face of a crisis than those which adopt a reactive or piecemeal approach to risk management. Thus, financial risk management can be understood as a vital foundation for corporate resilience, both in the short term to mitigate the impact of a crisis and in the long term to build business sustainability amidst an increasingly uncertain business environment.